Instances of Error in the Book Al-Iqlid and its Commentary Sharh Al-Mufassal by Al-Jandi (d. 669 AH) - Fawwaz, Mahmood Abdul Lateef; Hamad, Mahmoud Khalaf (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to examine Al-Jandi’s approach to error and correction in his book Al-Uqlid, exploring its significance in enhancing the grammatical framework. It seeks to highlight how Al-Jandi uses errors to engage scholars, clarify disagreements, and provide judgments on linguistic opinions presented in Al-Uqlid’s Sharh Al-Mufassal. The study also evaluates and analyzes these judgments to determine their impact on linguistic discourse. Methods: The study employs a descriptive and analytical approach, using established critical standards and terminology from linguistic criticism. This methodology allows for a structured examination of the linguistic errors and corrections discussed in Al-Jandi’s work. Results: The study clarifies the criteria for identifying linguistic errors and their corrections. It highlights instances where scholars either acknowledge or obscure their errors, citing expressions such as "some Kufans said," "some scholars said," and similar formulations. These expressions are used to categorize differing linguistic opinions without explicitly naming the scholars involved. Conclusion: The study reveals the framework for error and correction within linguistic criticism, using Al-Uqlid and its Sharh Al-Mufassal as a case study. It demonstrates that linguistic criticism is based on various standards, where errors are identified and corrected through structured dualities, offering a clear path for guidance in linguistic analysis.